Sustained impact of energy-dense TV and online food advertising on children's dietary intake: a within-subject, randomised, crossover, counter-balanced trial - Jennifer Norman; Bridget Kelly; Anne-T McMahon; Emma Boyland; Louise A. Baur; Kathy Chapman; Lesley King; Clare Hughes; Adrian Bauman (BMC, 2018)
Abstract Background Policies restricting children's exposure to unhealthy food marketing have been impeded by the lack of evidence showing a direct link between food advertising exposure and children's energy intake and body weight. Food advertising exposure increases children's immediate food consumption, but whether this increased intake is compensated for at later eating occasions is not known; consequently the sustained effect on diets remains unclear. Methods We conducted a within-subject, randomised, crossover, counterbalanced study across four, six-day holiday camps in New South Wales, Australia between April 2016 and January 2017. Children (7-12 years, n = 160) were recruited via local schools, email networks and social media. Two gender- and age-balanced groups were formed for each camp (n = 20), randomised to either a multiple- or single- media condition and exposed to food and non-food advertising in an online game and/or a television cartoon. Children's food consumption (kilojoules) was measured at a snack immediately after exposure and then at lunch later in the day. Linear mixed models were conducted to examine relationships between food advertising exposure and dietary intake, taking into account gender, age and weight status. Results All children in the multiple-media condition ate more at a snack after exposure to food advertising compared with non-food advertising; this was not compensated for at lunch, leading to additional daily food intake of 194 kJ (95% CI 80-308, p = 0.001, d = 0.2). Exposure to multiple-media food advertising compared with a single-media source increased the effect on snack intake by a difference of 182 kJ (95% CI 46-317, p = 0.009, d = 0.4). Food advertising had an increased effect among children with heavier weight status in both media groups. Conclusion Online ('advergame') advertising combined with TV advertising exerted a stronger influence on children's food consumption than TV advertising alone. The lack of compensation at lunch for children's increased snack intake after food advertising exposure suggests that unhealthy food advertising exposure contributes to a positive energy-gap, which could cumulatively lead to the development of overweight. Trial registration Australian New Zealand Clinical Trials Registry, number ACTRN12617001230347 (Retrospectively registered).